PARADISE 24: A Measure to Assess the Impact of Brain Disorders on People's Lives. - Alarcos Cieza; Carla Sabariego; Marta Anczewska; Carolina Ballert; Jerome Bickenbach; Maria Cabello; Ambra Giovannetti; Teemu Kaskela; Blanca Mellor; Tuuli Pitkänen; Rui Quintas; Alberto Raggi; et al. (PLoS ONE)
Objective To construct a metric of the impact of brain disorders on people's lives, based on the psychosocial difficulties (PSDs) that are experienced in common across brain disorders. Study design Psychometric study using data from a cross-sectional study with a convenience sample of 722 persons with 9 different brain disorders interviewed in four European countries: Italy, Poland, Spain and Finland. Questions addressing 64 PSDs were first reduced based on statistical considerations, patient's perspective and clinical expertise. Rasch analyses for polytomous data were also applied. Setting In and outpatient settings. Results A valid and reliable metric with 24 items was created. The infit of all questions ranged between 0.7 and 1.3. There were no disordered thresholds. The targeting between item thresholds and persons' abilities was good and the person-separation index was 0.92. Persons' abilities were linearly transformed into a more intuitive scale ranging from zero (no PSDs) to 100 (extreme PSDs). Conclusion The metric, called PARADISE 24, is based on the hypothesis of horizontal epidemiology, which affirms that people with brain disorders commonly experience PSDs. This metric is a useful tool to carry out cardinal comparisons over time of the magnitude of the psychosocial impact of brain disorders and between persons and groups in clinical practice and research.